Sugar conditioning combined with nectar nonsugar compounds enhances honey bee pollen foraging in a nectarless diocious crop - Facundo Verellen; Florencia Palottini; M. Cecilia Estravis-Barcala; Walter M. Farina (Scientific Reports)
Abstract Recently, it has been shown that sugar‑conditioned honey bees can be biased towards a nectarless dioecious crop as kiwifruit. The challenges for an efficient pollination service in this crop species are its nectarless flowers and its short blooming period. It is known that combined non-sugar compounds (NSCs) present in the floral products of different plants, such as caffeine and arginine, enhance olfactory memory retention in honey bees. Additionally, these NSCs presented in combination with scented food improve pollination activity in nectar crops. Here, we evaluated the effect of kiwifruit mimic-scented sugar solution (KM) on colonies located in this crop by supplementing them either with these NSCs individually (KM + CAF, KM + ARG), or combined (KM + MIX). Our results show an increase in colonies’ activity after feeding for all treatments. However, the colonies supplemented with the combined mixture (KM + MIX) collected heavier kiwifruit pollen loads and showed an increasing pollen stored area in their hives compared to the KM-treated control colonies. Unexpectedly, the caffeine-treated colonies showed a decrease in the pollen foraging related responses. These results show a combined effect of NSCs that improves honey bee pollen foraging in a nectarless crop, however this activity is impaired when caffeine is used alone for a nectarless crop.